An overview of ESP and EAP in language pedagogy - Papadima, Ourania (Categories and Units in Language and Linguistics, 2020)
The English language is widely used in educational institutes around the world, and especially in Higher Education. This has led to the development of English for Academic Purposes (EAP), a new branch within the field of English for Specific Purposes (ESP). This chapter is aimed at providing a conceptual framework for ESP and EAP. To this end, the chapter will focus on the diachronic development of ESP, the differences between ESP, EAP and EOP (English for Occupational Purposes), and the distinction of EAP in EGAP (English for General Academic Purposes) and ESAP (English for Specific Academic Purposes). Relevant key concepts in English language pedagogy, such as curriculum and syllabus design, as well as current issues in the field of EAP research, are also examined.